(untitled) (Research, Society and Development, 2022)
This article proposes an approach to the problems presented in teaching, not taking into account the motivation in the school and the teacher’s preparation to assume the pedagogical role in higher education, taking into account the environment in consideration the classification of the different objectives and skills that educators define for their students through Bloom’s taxonomy and Dreyfus’ skill acquisition that the longer the rules and procedures are followed, the learner becomes more experienced and more competent in a job or task. The educational one is based on the Design Science concepts that have the creation of defenders, that is, something that was created by man with the aim of improving people’s lives among others. The science of design aims to create advocates to build new realities and new knowledge.